Homogeneous and Non-homogeneous media indentification and circuitry design of multiphase Ultrasonic Tomography - Mohd Rizal, Manan; Mohd Hafiz, Fazalul Rahiman; Sazali, Yaacob; Ruzairi, Abdul Rahim (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.